The phenomenology of psilocybin's experience mediates subsequent persistent psychological effects independently of sex, previous experience, or setting - Klučková, Tereza; Nikolič, Marek; Tylš, Filip; Viktorin, Vojtěch; Vejmola, Čestmír; Viktorinová, Michaela; Bravermanová, Anna; Androvičová, Renáta; Andrashko, Veronika; Korčák, Jakub; Zach, Peter; Hájková, Kateřina; et al. (Pharmacological reports, 2025)
BACKGROUND: Recent studies intensively explore psilocybin's antidepressant potential, but variables like previous experience, repeated use, setting, and sex remain underexplored. This study examines acute and long-term effects of psilocybin in healthy individuals. METHODS: A double-blind, placebo-controlled, cross-over study included 40 healthy participants (20 females, mean age 38). Each received two doses of psilocybin (0.26 mg/kg) at least 56 days apart (mean 488) in two neuroimaging study arms. Nearly half had previous psychedelic experience. Acute effects were measured using the Altered States of Consciousness Scales (ASCs) and a Visual Analogue Scale (VAS) for emotional valence. The Persisting Effects Questionnaire (PEQ) assessed long-term effects. RESULTS: All results were independent of observed variables such as previous psychedelic experience, repeated use, setting, sex and occupation. Acute effects were moderate on the ASCs, with VAS ratings showing mostly pleasant or fluctuating experiences and only one unpleasant session. All experiences resolved in a positive or neutral state by the session's end. Psilocybin produced lasting positive effects across all PEQ domains, with negligible negative effects. Oceanic Boundlessness (OBN) and Visionary Restructuralization (VRS) correlated with positive outcomes, while Dread of Ego Dissolution (DED), typically associated with fear, did not predict negative effects. The nature of the acute experience (pleasant or mixed) was not linked to the direction or intensity of long-term outcomes. Peak experiences ending in a positive mood were strongly associated with favourable long-term effects. CONCLUSION: Repeated psilocybin administration in healthy individuals induces positive, lasting effects, with challenging experiences in controlled settings not causing adverse outcomes. These findings support psilocybin's psychological safety and its repeated use in clinical trials.
Keywords: Young Adult; Consciousness; halucinogeny; Male; emoce; vědomí; mladý dospělý; klinické křížové studie; sexuální faktory; Emotions; Adult; Sex; psilocybin; dospělí; mužské pohlaví; Healthy population; Hallucinogens; dvojitá slepá metoda; lidé; ženské pohlaví; Humans; Sex Factors; Psilocybin; Repeated administration; Previous experience; Cross-Over Studies; Double-Blind Method; Female; lidé středního věku; Middle Aged